Effectiveness of an educational program on paramedic knowledge and practice concerning pre-hospital burns management for adult at ambulance in Baghdad city - Rahman Jassm Al Jubouri, Hassan; Mohammed K, Khalida (International Journal of Psychosocial Rehabilitation, 2020)
Objective: to evaluate effectiveness of an educational program on paramedic knowledge and Practice concerning adult pre-hospital burns cases care at Ambulance Department in Baghdad City, to identify the association between Effectiveness of an Educational Program and the demographic characteristics of the paramedic (Age, Education Level and Years of Experiences).Methodology: Quantitative research uses quasi-experimental design to evaluate the effectiveness of an educational program on paramedic knowledge and practice concerning pre-hospital burns management for adult at ambulance in Baghdad city. The study was initiated (1ft October 2019 to 15th March 2020) Nonprobability (purposive) sample of (60) paramedic was selected from the ambulance department in Baghdad city. (30) paramedic for the study, which were exposed to the education program about pre-hospital burns management for adult, and (30) paramedic have been assigned to the control group who share the same criteria of selection for the study group and are not exposed to the educational program. the instruments was constructed by using a questioner which composed of three parts First Part: The demographic data: This included the Paramedic characteristic, such as gender, age, level of education, years of experience, and training. the second part: Knowledge test (40). The third part: Observational checklist. It is composed of (29) items. The validity of the questionnaire, Observational checklist and educational program were been identified by a panel of 13 experts; the reliability has been identified by adopting a pilot study carried out on (20th November to 11th December 2019). Data were analyzed the through application of descriptive statistics analysis and the inferential data.Result: The current study show that were a highly significant differences between the study and the control group, post applying educational program to knowledge and practice concerning pre-hospital burn management for adult.Conclusion: A there are significant effectiveness of educational program on paramedic knowledge and practice concerning pre-hospital burn management for adult at ambulance in Baghdad City.Recommendations: Approving the program training in the disaster and reginal training center for Emergency Medicine.